2003
DOI: 10.1046/j.1365-2672.2003.01832.x
|View full text |Cite
|
Sign up to set email alerts
|

The response of Leuconostoc mesenteroides to low external oxidoreduction potential generated by hydrogen gas

Abstract: Aims:The physiological consequences of low external oxidoreduction potential in Leuconostoc mesenteroides were investigated. Methods and Results: Leuconostoc mesenteroides was grown under two initial oxidoreduction potential conditions (E h7 : +200 mV and )400 mV) using nitrogen and hydrogen as reducing agents. Growth was affected by E h7 ; the lag phase increased from 1 h at an initial E h7 of +200 mV to 6 h at an initial E h7 of )400 mV; the maximum specific growth rate at )400 mV was 68% of the one observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…The preferred ORP range of the mutant shifted from around Ϫ190 mV to Ϫ280 mV (Fig. 5), suggesting not only different species or strains (7,30,31) but also that the mutants of the same strain had significantly different preferred ORP ranges. In comparison with the parent strain, the highest cell concentration and 1,3-PD production of the mutant strain were enhanced by 68.0% and 63.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preferred ORP range of the mutant shifted from around Ϫ190 mV to Ϫ280 mV (Fig. 5), suggesting not only different species or strains (7,30,31) but also that the mutants of the same strain had significantly different preferred ORP ranges. In comparison with the parent strain, the highest cell concentration and 1,3-PD production of the mutant strain were enhanced by 68.0% and 63.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The parameter that we used to develop this screening approach was redox potential (oxidoreduction potential [ORP]). Recently, ORP has been used as a parameter to investigate mass and energy metabolic fluxes in several microorganisms (7,26,30). It has been reported that each species, or even each strain, has a preferred redox potential range.…”
mentioning
confidence: 99%
“…Decreased ORP levels also improved the xylitol yield of stationary-phase fermentation by Candida tropicalis (19). Therefore, the extracellular ORP is a useful parameter for monitoring and regulating microbial metabolism in anaerobic or microaerobic processes (4,12,13,(19)(20)(21)(22)24).However, the physiological response of microbial cells to ORP alterations remains unclear. ORP changes may affect cellular physiology by altering intracellular redox levels (4), affecting the expression of individual enzymes (16,25) and changing the oxidative states of protein thiol groups.…”
mentioning
confidence: 99%
“…The ORP quantifies the redox property of solutions (11) and is a primary affecter of (facultative) anaerobic growth and metabolism (4,(12)(13)(14)(15)(16)(17). Generally, each microbial species optimally grows within a certain ORP range (14-16), and alteration of extracellular ORP usually leads to metabolic flux redistribution.…”
mentioning
confidence: 99%
See 1 more Smart Citation